Framing Detik.com dalam Pemberitaan Penganiayaan David - Carlos Antonio Lopulalan; Dyva Claretta (Universitas Batanghari Jambi, 2023)
The widespread news coverage of an assault case committed by Mario Dandy against the victim David has attracted public attention. This news has elicited various responses from the public towards the behavior of the son of the director general of taxes Rafael Alun Trisambodo, so many media outlets have reported this case from different perspectives. This study aims to find out the news framing (framing) about David's assault on Detik.com. This study uses a qualitative approach with Robert N. Entman's framing analysis method. With this method, the researcher found that Detik.com focused more on the motive and chronology of the assault, background, and identity of the perpetrator and victim. In addition, Detik.com is suspected of giving special treatment to AG or Agnes by disguising her identity and showing a child legal justice system that is unfair and ineffective. Furthermore, Media Detik.com reported the violence experienced by David as an intolerable act, especially if the assault occurred to a woman. Media detik.com also gave different coverage by bringing various sources in each news. As a suggestion, Detik.com should be careful in writing news so as not to be wrong in facts. In addition, news readers should be alert when reading the news because a wide insight is needed to understand the case reported by online media.